Business Administration In The Digital Era: Challenges And Opportunities In Facing Technological Disruption - Dasep Supriatna (Jurnal Riset Multidisiplin Edukasi, 2025)
This research investigates the challenges and opportunities in business administration arising from technological advances in the digital age. Using  a mixed-methods approach, this study examines organizational adaptability, innovation strategies, and structural change across industries. These findings reveal significant impacts of technological disruption, including increased agility, increased collaboration, and barriers such as cultural inertia and resource constraints. Theoretical frameworks, including Resource-Based View and Dynamic Capabilities, support analysis, offer actionable insights to foster resilience and leverage digital technologies for competitive advantage amid ever-evolving external pressures.